PROTOTYPING ROBOTIC MEDICAL REHABILITATION DEVICES (Nonconventional Technologies Review, 2017)
This paper will be presenting research and development stages of robotic rehabilitation devices. The focus of rehabilitation are aimed for the human hand, mainly for regaining motor functions by the aid of robotics. As part of the project a series of parts were designed around anthropometric measurements were used from previous work to design the prototype parts in the robotic rehabilitation device. In this paper non conventional fabrication methods were used such as fused filament fabrication to obtain the prototype parts. Research was done on materials to determine the optimum filament material for the application. Testing and configuration of the fabrication process was done gradually with the final result being presented in this paper.
Keywords: Fused filament fabrication; robotic rehabilitation device; robotic exoskeleton